The Lucy variations - Zarr, Sara 1970- (Little, Brown, 2014)
"Sixteen-year-old San Franciscan Lucy Beck-Moreau once had a promising future as a concert pianist. Her chance at a career has passed, and she decides to help her ten-year-old piano prodigy brother, Gus, map out his own future, even as she explores why she enjoyed piano in the first place."--